Potential Interplay between Hyperosmolarity and Inflammation on Retinal Pigmented Epithelium in Pathogenesis of Diabetic Retinopathy - Willermain, François (Int J Mol Sci, 2018)
Diabetic retinopathy is a frequent eyesight threatening complication of type 1 and type 2 diabetes. Under physiological conditions, the inner and the outer blood-retinal barriers protect the retina by regulating ion, protein, and water flux into and out of the retina. During diabetic retinopathy, many factors, including inflammation, contribute to the rupture of the inner and/or the outer blood-retinal barrier. This rupture leads the development of macular edema, a foremost cause of sight loss among diabetic patients. Under these conditions, it has been speculated that retinal pigmented epithelial cells, that constitute the outer blood-retinal barrier, may be subjected to hyperosmolar stress resulting from different mechanisms. Herein, we review the possible origins and consequences of hyperosmolar stress on retinal pigmented epithelial cells during diabetic retinopathy, with a special focus on the intimate interplay between inflammation and hyperosmolar stress, as well as the current and forthcoming new pharmacotherapies for the treatment of such condition.